Non-HDL Cholesterol and LDL Cholesterol as Main Risk Factors for Coronary Heart Disease: Meta-Analysis - Ravell Hansen Untono; Jusak Nugraha; I. Gde Rurus Suryawan; Andrianto Andrianto (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2022)
Coronary heart disease is a highly frequent illness in both developed and developing nations. Non-HDL cholesterol (n-HDL-c) and LDL cholesterol (LDL-c) stages are biomarkers that doctors frequently utilize to assess the risk of Coronary Heart Disease (CHD). This study was a systematic review and meta-analysis to assess the association between n-HDL-c and LDL-c as major risk factors for CHD. Cochrane, PubMed, and Science Direct searches were conducted using the keywords "LDL cholesterol," "non-HDL cholesterol," and "coronary heart disease." Any research that describes the analysis of LDL-c and n-HDL-c as key risk factors for CHD and all studies involving patients diagnosed with CHD are included in the literature. A total of seven papers were involved in the qualitative analysis (systematic review), while five studies were included in the quantitative analysis (meta-analysis). The English-language research includes two RCTs, four case-control studies, and one cohort study, with a total of 68,713 individuals. LDL-c parameters were obtained (MD = 8.45; 95 percent CI = 7.03-9.87 p=0.001) and n-HDLc (p=0.001) (MD = 35.57; 95 percent CI = 33.27-37.88). n-HDL-c may be a more significant parameter of CHD risk because it has a higher MD value.